DEMONSTRATION METHOD TO TEACH WRITING PROCEDURE TEXT - Dedek Aditia; Octa Sinar Anisah Dian; Herni Mayang Sari (English Education Study Program FKIP Universitas Alwashliyah Medan, 2023)
This article describes how demonstration method can be used to teach writing procedures text for students in English subject. Demonstration method applies creative and active teaching process that can motivate students to engage the learning process. Teaching English in writing procedures text is not easy. Demonstration method activities require the teachers to perform a demonstration of a process to make or create something. Therefore, teaching writing procedure text in English using demonstration method needs preparation. It is expected that this method can be a suitable method for teachers and students in mastering writing procedure text in English.